Trends in Outcomes of a Prospective Consecutively Enrolled Single-Center Adult Cervical Deformity Series. Issue 24 (15th December 2022) - Passias, Peter G.; Passfall, Lara; Imbo, Bailey; Williamson, Tyler; Joujon-Roche, Rachel; Krol, Oscar; Tretiakov, Peter; Kummer, Nicholas A.; Sagoo, Navraj; Lanre-Amos, Tomi; Schoenfeld, Andrew J.; De La Garza, Rafael; et al.
Abstract : Study Design: Retrospective cohort. Objective: The aim was to describe the two-year outcomes for patients undergoing surgical correction of cervical deformity (CD). Background: Adult CD has been shown to compromise health-related quality of life. While advances in spinal realignment have shown promising short-term clinical results in this parameter, the long-term outcomes of CD corrective surgery remain unclear. Materials and Methods: Operative CD patients >18 years with two-year (2Y) health-related quality of life/radiographic data were included. Improvement in radiographic, neurologic, and health-related quality of life outcomes were reported. Patients with a prior cervical fusion and patients with the greatest and smallest change based on Neck Disability Index (NDI), numeric rating scale (NRS) neck, modified Japanese Orthopaedic Association (mJOA) were compared using multivariable analysis controlling for age, and frailty, and invasiveness. Results: One hundred and fifty-eight patients were included in this study. By 2Y, 96.3% of patients improved in Ames cervical sagittal vertical axis modifier, 34.2% in T1 slope minus cervical lordosis (TS-CL), 42.0% in horizontal gaze modifier, and 40.9% in SVA modifier. In addition, 65.5% of patients improved in Passias CL modifier, 53.3% in TS-CL modifier, 100% in C2-T3 modifier, 88.9% in C2S modifier, and 81.0% in MGS modifier severity by 2Y. The cohort significantly improved from baseline to 2Y in NDI, NRS Neck, and mJOA, all P <0.05. 59.3% of patients met minimal clinically important difference for NDI, 62.3% for NRS Neck, and 37.3% for mJOA. Ninety-seven patients presented with at least one neurologic deficit at baseline and 63.9% no longer reported that deficit at follow-up. There were 45 (34.6%) cases of distal junctional kyphosis (DJK) (∆DJKA>10° between lower instrumented vertebra and lower instrumented vertebra-2), of which 17 were distal junctional failure (distal junctional failure-DJK requiring reoperation). Patients with the greatest beneficial change were less likely to have had a complication in the two-year follow-up period. Conclusion: Correction of CD results in notable clinical and radiographic improvement with most patients achieving favorable outcomes after two years. However, complications including DJK or failure remain prevalent.